Figuraties : 1900-2000. - Becker, Wolfgang; Bisscheroux, Sander (Heerlen : Algemeen Burgerlijk Pensioenfonds, 2000)
van Dongen, Kees ; Gutfreund, Oto ; Sluijters, Jan ; Toorop, Charlie ; Loeber, Lou ; Derain, André ; Lindström, Beng ; Appel, Karel ; Mooy, Jaap ; Visser, Carel ; et al.
Figuraties 1900-2000, Heerlen
kunstcatalogus